Informasi Diagnostik Pemeriksaan Appendikografi Oral dan USG dalam Menegakkan Diagnosis Appendisitis - Agustina Dwi Prastanti; Darmini Darmini; Andrey Nino Kurniawan (Jurnal Imejing Diagnostik (JImeD), 2021)
Background: Patients with suspected appendicitis are always asked by the sending doctor (Pediatric Surgeon) to ask for an oral appendicography examination without seeking other investigations such as ultrasound or CT scan. Whereas in the oral appendicography examination, false negative often occurs so that the patient is exposed to radiation several times until the barium reaches the caecum area and no more barium is still in the small intestine. Compared to the oral appendicography examination, ultrasound examination is easier in patient preparation, cheaper in terms of cost and more safety against the dangers of X-ray radiation.Methods: This research is a descriptive analytic study conducted with a cross sectional approach. The study was conducted by providing interventions for ultrasound examination before carrying out an oral appendicography examination. Ultrasound examination of the appendix is an examination using ultrasound waves with a frequency of 5-7.5 MHz or 2-4 MHz to diagnose appendicitis. Oral appendicography examination is a radiological examination to confirm the diagnosis of appendicitis using 100 grams of barium sulfate contrast medium diluted to a volume of 200 ml that is administered orally.Results: Diagnostic information obtained on oral appendicography examination of suspected appendicitis in radiology department Roemani Hospital, among others, can show the presence of calcification and the length of the appendix organs can be measured. Diagnostic information obtained on ultrasound examination of suspected appendicitis, among others, can show the presence of debris (pus), can evaluate the thickness of the intestinal wall and its vascularity.Conclusion: Ultrasound examination for suspected appendicitis is the first choice in diagnosing appendicitis than oral appendicography because it can be done in a faster, safer, more convenient and non-invasive manner and the cost of ultrasound is cheaper than oral appendicography.